Islamic financial ethics - Musa, Muhammad Adli (2013)
The recent financial crises testify that the lack of ethics in financial businesses has malignant effects on economic activity as a whole. Moreover, finance has developed into a subfield of economics and the distinction between the ethical concerns of economics and the ethical concerns of finance has become increasingly irrelevant. Interestingly, financial ethics is considered a subfield of business ethics rather than a subfield of finance or economics due to the voluminous amount of research devoted to financial ethics by non-finance scholars, who are mostly business ethicists. Financial ethics as an academic field is concerned with the moral issues that arise in finance theory, financial markets, financial services and financial management. It is claimed that Islamic finance, which is gaining recognition as a component of the global financial system, can play a role in establishing a sense of ethics that has been lost within the broader financial system. In this paper I look at Islamic financial ethics with particular reference to Islamic financial services. Based on the literature on Islamic business ethics and Islamic finance, I present a framework of Islamic financial ethics for Islamic financial institutions. Building upon three main guiding principles of Islamic business ethics, which I identify to be God-consciousness, justice and benevolence, I present ethical norms which should govern the activities of Islamic financial institutions. I conclude that Islamic financial institutions should not Islamise every financial practice but emphasise on the social and economic end of financial transactions in order to provide a genuine alternative to the current operating financial systems.